Civil liability in Europe for terrorism-related risk / Lucas Bergkamp, Michael Faure, Monika Hinteregger and Niels Philipsen. - Bergkamp, Lucas; Faure, Michael (Michael G.); Hinteregger, Monika; Philipsen, Niels, 1975- (Cambridge studies in international and comparative law (Cambridge, England : 1996) ;, 2015)
Today terrorism has become a world-wide phenomenon which does not stop at the European borders. Following the 9/11 attacks on the World Trade Centre and terrorist attacks in Paris, Madrid and London, concerns have arisen in Europe about potential liability exposure for terrorism-related damage. This book tackles the problem of civil liability for damage caused by terrorist acts from several angles. The authors expertly deliver a comprehensive analysis of terrorism-related risk under international and EU law and the national tort law systems of seven representative EU Member States. They also provide a comparison of the situation in Europe to the liability environment in the US. Risk mitigation strategies are considered and critically assessed, as are alternative systems for redressing terrorism-related risks. The book concludes with a reflection on the analysis and presents possible strategies for future regulation by the European lawmakers.